High glucose increases caspase-dependent apoptosis in inner medullary collecting duct (IMCD) cells, independent of prostaglandin E(2) (PGE2) - Dougherty, Monika (University of Ottawa (Canada), 2005)
Hyperglycemia is the main determinant of diabetic nephropathy, resulting in altered renal cell growth and tubular atrophy. Additionally, prostaglandin synthesis is elevated in the diabetic kidney and may play a role in antagonizing or mediating the effects of glucose on cell growth and death. Recently, our laboratory reported that high glucose increases PGE 2 synthesis in IMCD cells, consequently, this study will determine the effect of high glucose and PGE2 on IMCD cell growth and apoptotic death. After four days high glucose exposure, there was a decrease in DNA and protein synthesis compared to low glucose. Concomitantly, high glucose treatment increased the percentage of IMCD cells displaying fragmented DNA characteristic of apoptosis, which was significantly attenuated by treatment with a pan-caspase inhibitor. Caspase-3 and/or caspase-7 activity was also augmented after four days high glucose treatment, and there was an observed increase in the expression of Bax to Bcl-2. These effects were partially mimicked by mannitol treatment. Although PGE2 treatment increased DNA and protein synthesis in the presence of indomethacin, neither indomethacin nor PGE2 altered the apoptotic response of IMCD cells in low or high glucose. To our knowledge, this study is the first to show that high glucose treatment induces IMCD cell apoptosis, coincident with a decrease in DNA and protein synthesis, and independent of PGE2.
Keywords: Biology, Molecular.; Biology, Cell.; Chemistry, Biochemistry.